Recurring epistaxis as a result of a massive inverted papilloma of the sinonasal region - Tadić Teodora; Jovanović Anđelina; Valjarević Svetlana; Jovanović Milan B. (Halo 194, 2023)
Introduction: Inverted papilloma is the most common benign tumour of the sinonasal region characterized by a locally destructive growth pattern, a tendency to recur, and a risk of malignant alteration. It grows from the epithelium of the sinonasal mucosa. One of its clinical signs is epistaxis, which is an emergency condition. This case report aims to acquaint Emergency Medicine physicians with inverted papilloma as an emergency condition in some patients. Case report: A 75-year-old woman presented to our Ear, Nose and Throat Emergency Room complaining of repetitive left-sided nose bleeds. Clinically, histopathologically, and using radiology scans, we confirmed the diagnosis of inverted papilloma and the patient was surgically treated. Conclusion: In patients with recurrent nose bleeds, an accurate diagnosis of inverted papilloma is needed for planning surgical treatment to avoid recurrence, local destruction and malignant alteration of the tumour.